Proteomic Signatures of Antimicrobial Resistance in Yersinia pestis and Francisella tularensis - Deatherage Kaiser, Brooke L.; Birdsell, Dawn N.; Hutchison, Janine R.; Thelaus, Johanna; Jenson, Sarah C.; Andrianaivoarimanana, Voahangy; Byström, Mona; Myrtennäs, Kerstin; McDonough, Ryelan F.; Nottingham, Roxanne D.; Sahl, Jason W.; Schweizer, Herbert P.; et al. (Frontiers in Medicine, 2022)
Antimicrobial resistance (AMR) is a well-recognized, widespread, and growing issue of concern. With increasing incidence of AMR, the ability to respond quickly to infection with or exposure to an AMR pathogen is critical. Approaches that could accurately and more quickly identify whether a pathogen is AMR also are needed to more rapidly respond to existing and emerging biological threats. We examined proteins associated with paired AMR and antimicrobial susceptible (AMS) strains of Yersinia pestis and Francisella tularensis, causative agents of the diseases plague and tularemia, respectively, to identify whether potential existed to use proteins as signatures of AMR. We found that protein expression was significantly impacted by AMR status. AMR-conferring proteins were expressed even in the absence of antibiotics in growth media, and the abundance of 10-20% of cellular proteins beyond those that directly confer AMR also were significantly changed in both Y. pestis and F. tularensis. Most strikingly, the abundance of proteins involved in specific metabolic pathways and biological functions was altered in all AMR strains examined, independent of species, resistance mechanism, and affected cellular antimicrobial target. We have identified features that distinguish between AMR and AMS strains, including a subset of features shared across species with different resistance mechanisms, which suggest shared biological signatures of resistance. These features could form the basis of novel approaches to identify AMR phenotypes in unknown strains.